Patterns of Family Conflicts in Kuwaiti Society - Al-Hajri, Ghaida; Altaii, Alaa; Guenifa , Nora (Al-Adab Journal, 2025)
The study aimed to identify the patterns of family conflicts in Kuwaiti society by employing the social survey method. To achieve the study’s objectives, a questionnaire was used as a research tool and administered to a purposive sample of 25 families in Kuwait. These families were selected from various social and economic backgrounds in the Jaber Al-Ahmad area of the Capital Governorate, based on records from the Community Development Center. The results indicated that the most prevalent type of family conflict in Kuwaiti society is conflicts of an educational nature, followed by economic conflicts, then conflicts related to the distribution of family time, emotional conflicts, and finally, behavioral conflicts. The study recommended encouraging families to adopt effective dialogue techniques to resolve conflicts constructively while avoiding negative communication.